The Use of Picture Books in Developing Language Skills of Children Aged 3–4 Years - Revi Dianita; I. Ismail (Manunggal Halim Jaya, 2026)
This study aimed to examine the effect of the picture book storytelling method on the language abilities of children aged 3–4 years and to observe the differences in language skills before and after the intervention. The research employed a pre-experimental design using a one-group pretest–posttest framework, and the statistical analysis applied was the paired t-test. The study sample consisted of 12 children aged 3–4 years at PAUD TP Harapan Jaya, with data collected through observation sheets. The results indicated a p-value of 0.000 (p < 0.05), demonstrating a significant effect of the picture book storytelling method on children’s language abilities. The mean language ability of the children before the intervention was 34.37%, which increased to 69.40% after the intervention. The study concluded that the use of picture books is effective in enhancing the language abilities of children aged 3–4 years.